Pengaruh Belanja Daerah Dan Kompetisi Politik Terhadap Pengungkapan Internet Financial Reporting (IFR) Pada Kabupaten/Kota Di Jawa Barat - Santi Nurhunah; Dedi Mulyadi; Yanti Yanti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of regional spending and political competition on Internet Financial Reporting Disclosures. There are 2 hypotheses tested namely (1) There is an influence between regional spending on disclosure of Internet Financial Reporting (2) There is an influence between political competition on disclosure of Internet Financial Reporting. The sample used in this study amounted to 135 districts/cities in West Java in 2017-2021. The sampling technique uses saturated sampling. Data processing in this study utilizes PLS-SEM on SmartPLS 4.0 software. The results of this study are (1) Regional spending effect on disclosure of Internet Financial Reporting in districts/cities in West Java Province (2) Political Competition effect on disclosure of Internet Financial Reporting in districts/cities in West Java Province Both hypotheses in this study are proven and accepted. Keywords: Regional Expenditure, Political Competition and Disclosure of Internet Financial Reporting